Vocal learning promotes patterned inhibitory connectivity - Mark N. Miller (Nature Portfolio, 2017)
Complex motor behaviors such as birdsong are learned through practice and are thought to depend on specific excitatory connectivity in premotor circuits. Here the authors show that song learning in Bengalese Finches is associated with enrichment of inhibitory network connectivity that can affect specific song features.